FRAMING ANALYSIS OF THE "BOCOR ALUS" PODCAST ON TEMPODOTCO YOUTUBE ACCOUNT, EPISODE: "JOKOWI'S MANEUVERS AHEAD OF STEPPING DOWN - Lestari, Suci Shinta; Putri, Natasya Ayuni (Journal of Digital Media Communication, 2025)
Social media, which has become a digital trend, has become an important tool in communication, especially in disseminating information that the media uses to convey issues and news, particularly political matters. In conveying information, the media frames an issue to influence public perception. This research aims to understand how Tempo frames the issue in the podcast Bocor Alus Politik episode "Maneuver Jokowi Jelang Lengser: Fufufafa dan Menolak PDIP." Entering KIM regarding the issue of Jokowi protecting Gibran Rakabuming Raka and political maneuvers in maintaining his position in the political world. This research theory uses Robert N. Entman's framing analysis, which consists of Define Problems, Diagnose Causes, Make Moral Judgement, and Treatment Recommendation. The research method used in this study is descriptive qualitative with the form of research being framing. The data collection techniques used in this study are obtrusive observation of podcast content and documentation based on excerpts of podcast content. The result of this research is that the Tempo in the Bocor Alus Politik podcast leads to a negative framing because Jokowi should not make strategic decisions at the end of his term.